Efectividad de las trampas amarillas para la captura de afidos en fruta Bomba (Carica papaya L.) - Hernandez Perez, R.
(En, Es)
ilus., 10 ref.
Keywords: CARICA PAPAYA; APHIDOIDEA; TRAMPAS; CUBA; AFIDOS; TRAMPAS AMARILLAS